Pemberdayaan Jemaat dan Pertumbuhan Gereja - Suhartono Suhartono (Sekolah Tinggi Agama Kristen Lentera Bangsa Manado, 2024)
Abstract: A healthy church is a church that experiences full growth both in quantity (quantity and distribution) and quality (spirituality that reflects the example of Christ). In a world that is currently facing various problems, especially related to the Covid-19 Pandemic, The Church cannot be silent or passive. Although the Church cannot solve every problem, at least the church can be part of the solution of some problems faced by the congregation and the surrounding community. A healthy church presence and its mission to empower communities are needed as solutions to today's global problems. This article uses a qualitative descriptive approach with a literature study approach to answer questions related to healthy churches and church empowerment tasks. From the study of various literature sources, it was found that there are at least 4 aspects that describe the characteristics of a healthy church: the increase in the number of congregations, the mission of evangelizing/pioneering new churches, spiritual growth, and church involvement in serving. This is to be viewed as part of a spiritual formation that shows Christlikeness and a longing to bring souls to Christ. This can be seen in the task of church empowerment which includes all church Citizen Service movements in the midst of churches and communities that are mutually constructive. Church empowerment includes elements of enabling, empowering, and charity. The empowerment of the congregation is comprehensive and included in the three tasks of the church, namely: koinonia, marturia, and diakonia. In conclusion, a healthy church is a church that grows in quantity and quality and leads movements that empower the church as a guide to life for the glory of Christ.Abstrak: Gereja yang sehat adalah gereja yang mengalami pertumbuhan yang utuh baik secara kuantitas (kuantitas dan sebaran) maupun kualitas (spiritualitas yang mencerminkan keteladanan Kristus). Di dunia yang saat ini menghadapi berbagai permasalahan, terutama terkait pandemi Covid-19, Gereja tidak bisa diam atau pasif. Meskipun Gereja tidak bisa menyelesaikan setiap permasalahan, setidaknya Gereja dapat menjadi bagian dari solusi beberapa permasalahan yang dihadapi jemaat dan masyarakat sekitar. Kehadiran Gereja yang sehat dan misinya untuk memberdayakan masyarakat diperlukan sebagai solusi terhadap permasalahan global saat ini. Artikel ini menggunakan pendekatan deskriptif kualitatif dengan pendekatan studi pustaka untuk menjawab pertanyaan terkait gereja sehat dan tugas pemberdayaan gereja. Dari kajian berbagai sumber pustaka, ditemukan minimal ada 4 aspek yang menggambarkan ciri-ciri gereja yang sehat: pertambahan jumlah jemaat, misi pengabaran Injil/perintisan gereja baru, pertumbuhan spiritual, dan keterlibatan jemaat dalam melayani. Hal ini harus dipandang sebagai bagian dari formasi spiritual yang menunjukkan keserupaan dengan Kristus dan kerinduan membawa jiwa kepada Kristus. Hal ini tampak dalam tugas pemberdayaan jemaat yang mencakup seluruh gerak pelayanan warga gereja di tengah-tengah jemaat dan masyarakat yang bersifat saling membangun. Pemberdayaan jemaat mencakup unsur enabling, empowering, dan charity. Pemberdayaan jemaat tersebut bersifat menyeluruh dan termasuk dalam tiga tugas gereja, yaitu: koinonia, marturia, dan diakonia. Kesimpulannya, gereja yang sehat adalah gereja yang bertumbuh secara kuantitas dan kualitas serta memimpin gerakan-gerakan yang memberdayakan gereja sebagai pedoman hidup untuk kemuliaan Kristus.